Clinicopathological analysis of splenic red pulp low‐grade B‐cell lymphoma. Issue 5 (12th February 2020) - Suzuki, Takaharu; Miyoshi, Hiroaki; Shimono, Joji; Kawamoto, Keisuke; Arakawa, Fumiko; Furuta, Takuya; Yamada, Kyohei; Yanagida, Eriko; Takeuchi, Mai; Seto, Masao; Sone, Hirohito; Takizawa, Jun; et al.
Abstract : Primary splenic low‐grade B‐cell lymphoma of the red pulp comprises hairy cell leukemia (HCL) and splenic B‐cell lymphoma/leukemia, unclassifiable (SPLL‐U). SPLL‐U is a rare disease that includes subtypes of a hairy cell leukemia‐variant (HCL‐v), splenic diffuse red pulp small B‐cell lymphoma (SDRPL) and other types that are known as narrow sense SPLL‐U (SPLL‐U‐NS). Notably, limited information is available regarding the BRAF mutation (V600E) and cyclin D3 expression in subtypes of SPLL‐U. Therefore, we performed a pathological analysis of the BRAF mutation (V600E) and characterized pathological features of SPLL‐U. We reviewed the pathological findings of 12 SPLL‐U cases. The 12 cases considered included two cases of HCL‐v, six cases of SPLL‐U‐NS and four undetermined cases. The BRAF mutation (V600E) was detected in three cases, which were all SPLL‐U‐NS. Cases with the BRAF mutation (V600E) have increased levels of CD103 expression and decreased cyclin D3 and cyclin D1 expression compared with cases that lacked the BRAF mutation. These findings suggest that the BRAF mutation might play a significant role in SPLL‐U. Therefore, the significance of the BRAF mutation should be evaluated via genomic or transcriptional analyses of a large cohort of SPLL‐U patients.